DEVELOPMENT OF A PHYSICAL ACTIVITY LEARNING MODEL MULTIMEDIA BASED IN FLOOD PROne AREAS - Rahmadi, Rahmadi; Indah, Eka Purnama; Rakhman, Arie (Riyadhoh : Jurnal Pendidikan Olahraga, 2023)
The background to this research comes from a school that adapts to natural situations, where sometimes when the tide is high it will submerge the entire school yard, causing physical education learning activities to be hampered. Based on survey results from the past 2 years, there are indeed several schools in the Banjar Regency area that have been submerged by high tides/are prone to flooding. The aim of this research is to create a learning model that is suitable for use during high tide by testing several learning models that have been designed related to multimedia-based physical activities. The method used in this research is research and deployment (RnD) with the ADDIE design (Analysis, Design, Development or Production, Implementation or Delivery and Evaluations). The research instruments used are tests and measurements, including testing learning models and finding out the results of validity tests and effectiveness tests. The research results show that the peer teaching and cooperative learning models are more dominantly used in flood conditions, but other variations of learning models also do not rule out the possibility of being used in post-floods with a usage intensity level of 73.5% for the peer teaching model and 73.1% for the cooperative model. dominantly used by physical education teachers at SMPN 2 Martapura Timur. In this way, these two learning models will provide activities for students with multimedia tools.